Analysis of Broadcast Communication Management in the Convergence of Linear Television and Digital Platforms at TvOne (Study of Consumption, Distribution, and Promotion Patterns of Two-Sided Programs on YouTube) - Siti Suhanah Wati; Prima Mulyasari Agustini (Sean Institute, 2025)
The transformation of the broadcasting industry in the digital era has shifted audience consumption patterns from linear television to digital platforms based on Video on Demand (VOD). This shift requires broadcasting institutions, including tvOne, to adjust their communication management to remain relevant to audience characteristics, particularly among younger generations. This study aims to analyze audience consumption patterns, content distribution models, and digital promotion programs of the Dua Sisi talk show on the tvOneNews YouTube channel. A qualitative case study approach was applied, with data collected through in-depth interviews, non-participant observation, and documentation of digital content. The findings indicate that Dua Sisi audiences are dominated by Generation Z and millennials who prefer the flexibility of YouTube over linear television. The distribution model includes full episodes, highlight segments, and short clips disseminated across multiple platforms. The digital promotion program employs flyers, teasers, community posts, and highlight content after broadcasts. This research emphasizes that broadcast communication management must adapt to the logic of platforms that prioritize Datafication, Connectivity, and interactivity in order to remain relevant and competitive in the digital media ecosystem.